Cloud stabilization of kalamansi juice (Citrus microcarpa Bunge) - Alcid, Grace L.; Gatchalian, Miflora M. (1981., 1981)
ABSTRACT The three-phase study dealt mainly with cloud stabilization of kalamansi juice. Phase I aimed to determine the factors which could affect cloud stability. Various factors such as pH, % tritable acidity, density, viscosity and pectin content were analyzed. Results of the objective tests shows that cloud instability in kalamansi juice seemed to be related mainly to extremely low pH and high tritable acidity of the juice. Phase II was involved in the determination of the optimum level of the best stabilizer. Single strength kalamansi juice and concentrated kalamansi juice with 0.1% citrus pectin gave the most stable cloud. The same samples were also considered most acceptable. The effect of storage at room temperature on the suspending ability of the best kind and amount of stabilizer chosen in Phase II was studied in the last phase. Results showed no significant effect on pH of control and experimental (with 0.1% citrus pectin)samples. Furthermore, storage had significant effect on viscosity of both control and experimental samples.
Thesis (BS Food Technology)--University of the Philippines Diliman.
Keywords: Citrus juice